Transformation of system in the library: Good or not? / Mazliana Ya and Yusni Hidayu Amran - Ya, Mazliana; Amran, Yusni Hidayu (Faculty of Information Management, 2014)
Library is a place which store of information. People need library in order to access the information and gain knowledge. In order to serve the information to the users, library itself should know their services and methods that are effective to distribute the information. Transformation in the library especially the system used are important to improve the library services and library image.